Data Exfiltration in Model Context Protocol (MCP)-Based Intelligent Agents: An Evaluation of Prompt Injection Vectors - Barcelos, Tuigg R.; Quincozes, Silvio E.; Souza, Paulo (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais do XXVI Simpósio Brasileiro de Cibersegurança, 2026)
The integration of Intelligent Agents utilizing Large Language Models (LLMs) with external systems via the Model Context Protocol (MCP) expands the capabilities of autonomous agents, but also introduces critical data exfiltration risks. This study empirically evaluates the native defenses of Intelligent Agents against direct technical commands and social engineering-based prompt injections. In 160 automated tests across eight models, the results indicate that current semantic alignment is insufficient: models resistant to direct orders became vulnerable in seemingly authorized contexts, exhibiting up to 40% data leakage, while security-oriented models reached up to 90% successful exfiltration of sensitive files. We conclude that MCP architectures should not rely solely on the safety barriers of the underlying model, requiring strict egress controls at the protocol layer.